THE DEVELOPMENT OF A NEW CONCEPT OF JUSTICE: THE NEED FOR THE INCLUSION OF PEOPLE WITH DISABILITIES IN THE FORMATION OF THE STATE WILL - Neder dos Santos, Erika; Serrão, Adriana (Revista Gênero e Interdisciplinaridade, 2023)
This study aims to present the need for a new vision of justice to include the rights, interests and objectives of people with disabilities in the formation of the state will. This new approach to justice that best defines the current diversity of individuals is martha nussbaum’s theory of capabilities. In addition to this new social perspective of justice, the study intends to analyze the international documents that defend and protect the rights of people with disabilities, and their values should also be observed for the guarantee of social justice.